Maqasid Al-Shariah as an Evaluative Framework for the Digitalisation of Islamic Education: (Contemporary Hermeneutic Approach Study) - Taofeeq Olamilekan Sanusi (Permata : Jurnal Pendidikan Agama Islam, 2025)
This research examines the dualism of challenges in digitalising Islamic education - the need to adopt technology to improve competitiveness versus the fear of erosion of traditional values and Islamic identity. Using a qualitative method with a contemporary hermeneutic approach and literature research type, this study conducts a comprehensive analysis of primary (classical works of Al-Ghazali, Al-Shatibi, Ibn Ashur) and modern (Jasser Auda, Mohammad Hashim Kamali, Ahmad Al-Raysuni) sources, as well as relevant secondary sources. The research results identified four models of Maqasid Al-Shariah reinterpretation in the context of the digitalisation of Islamic education: teleological-contextual (Jasser Auda), systemic-holistic (Mohammad Hashim Kamali), integration-interconnection (Amin Abdullah), and transformative-reconstructive (Ebrahim Moosa and Tariq Ramadan). The research also found that Maqasid Al-Shariah provides five main evaluative dimensions that can be applied in assessing the digitalisation of Islamic education: protection of religion (hifz al-din), protection of the soul (hifz al-nafs), protection of the intellect (hifz al-'aql), protection of offspring (hifz al-nasl), and safety of property (hifz al-mal). Keywords: Maqasid Al-Shariah; Evaluative Framework; Digitalization of Islamic Education